RETORIKA KHATIB DALAM PENYAMPAIAN KHUTBAH JUM’AT - luthfi yuhesdi; Bukhari Bukhari; Zainal Zainal; sarwan sarwan (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2019)
The background of this research is because of the reality in the field, that the Friday sermon delivered by the khatib has yet to have a good appeal in the sermon. The purpose of this study First is to know how the style of the khatib in the delivery of the Friday sermon, Secondly, to know how the choice of the word of the khatib in the delivery of the Friday sermon, Third, to know how the tone of the khatib in the delivery of Friday sermon, and Fourth, to learn how the sentence structure of the khatib in the delivery of the sermon of Friday. This study uses a qualitative research methodology with observation data collection techniques, and interviews. This study found that the application of rhetoric by the Friday khutib in the sermon had not fully progressed as most khatib had not yet understood rhetoric. This is evident from the diction applied by the khatib not in accordance with the condition of the congregation, the application of repetition of the word does not conform to the rules of repetition. And there's also a lot of words. The relationship between sentence one with another sentence still does not use the correct word. And the emphasis on what matters is still not seen. The intonation conveyed by the khatib has not produced the appropriate variation, then the presentation is still monotonous and creates the jema'ah friday.